Implikasi Dana Desa terhadap Peningkatan Pembangunan dan Pemberdayaan Masyarakat di Desa Pejeng Kelod Kecamatan Tampaksiring Kabupaten Gianyar - Dewa Putu Sukabawa; Karyoto Karyoto (Penerbit Goodwood, 2022)
Purpose: the purpose of this research is to know investigate and to analyze implication fund a village to improve development and fower society and to analyze the problems in the implementation found village and to investigate toward reports have been done by goverment to improve prosperity of pejeng kelod village Tampaksiring Subdistrict Gianyar Rigency. Method: This research is use yuridical empirical method that is method is to investigate to the aplicable legal provisions and what happened in the village with data collection technique in the comonity with interview, observation, documentation or references study and research online data with the airo of obtain accurate data. Result: This research to shows that implication fund village to the improvement of development and power society at Pejeng Kelod village Tampaksiring subdistrict and Gianyar regency very helpful to improve all the development and power society at pejeng kelod to improve the economic matters tucanbe make charge to their life to be a better life.